Updated operational models for long-range forecasts of Indian summer monsoon rainfall - THAPLIYAL, V.; RAJEEVAN, M. (MAUSAM, 2003)
Based on operational 16 parameter models, the India Meteorological Department, since 1989, has been issuing the long-range forecasts for monsoon rainfall (June-September) for the country as a whole. Qualitative forecasts of category of monsoon (deficient, normal and excess) proved accurate on all the 11 years (1989-99). However, the errors in the quantitative forecasts, particularly from 1996-99 were more than the model error of ± 4 %. Therefore the operational 16-parameter models (parametric and power regression) were updated by replacing four predictors whose relationship with monsoon rainfall has weakened in recent years. The new predictors introduced into the models are Arabian Sea SST, South Indian Ocean SST, Europe Pressure Gradient and Darwin Pressure Tendency. The model constants were recalculated with the data for the period 1971-95. The performance of the updated model was found to be far better especially during the recent years. The absolute mean error of the forecasts from the updated model for the period 1991-99 was 3.2 % as against 7.0 % of the operational forecasts. As these updated models showed promise, they were introduced in 2000 for issuing the operational long-range forecasts of Indian summer monsoon rainfall.